2019
DOI: 10.1186/s12906-019-2649-7
|View full text |Cite
|
Sign up to set email alerts
|

Solid state fermentation process with Aspergillus kawachii enhances the cancer-suppressive potential of silkworm larva in hepatocellular carcinoma cells

Abstract: Background Mulberry silkworm larvae ( Bombyx mori ) are known as the oldest resource of food and traditional medicine. Although silkworm larvae have been reported to treat various chronic diseases, the effect of fermentation by microorganisms improving the biological activities of silkworm larvae was not reported. In the present study, fermented silkworm larvae was developed via solid-state fermentation with Aspergillus kawachii and investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Available studies have employed starter cultures (mainly bacteria and fungi culture) in either submerged or solid-state fermentation at varying conditions to enable bio-modification of inherent components of edible insects. Among the few experimental studies, solid state fermentation of dried Bombyx mori larvae using Aspergillus kawachii as starter culture was reported to show higher fatty acid and lower amino acid and mineral contents [66]. Ethanol extracts from the resultant sample was therapeutically demonstrated to induce improved cancer inhibitory effects in human hepatocellular carcinoma cells through modification of secondary metabolites.…”
Section: Fermentation Of Edible Insectmentioning
confidence: 99%
“…Available studies have employed starter cultures (mainly bacteria and fungi culture) in either submerged or solid-state fermentation at varying conditions to enable bio-modification of inherent components of edible insects. Among the few experimental studies, solid state fermentation of dried Bombyx mori larvae using Aspergillus kawachii as starter culture was reported to show higher fatty acid and lower amino acid and mineral contents [66]. Ethanol extracts from the resultant sample was therapeutically demonstrated to induce improved cancer inhibitory effects in human hepatocellular carcinoma cells through modification of secondary metabolites.…”
Section: Fermentation Of Edible Insectmentioning
confidence: 99%
“…Plant-based fermented foods are produced using substrates like cereals, legumes, fruits and vegetables, whereas dairy, meat and fishes are applied for production of animal-based fermented products [83]. Attempt on fermentation of certain edible insects shows increased shelf life [84], enhanced nutrition content [85][86][87][88][89] improved taste [90,91] and reduction of microbial contamination risk [92]. The fermentation process of edible insects and its benefits are presented Fig.…”
Section: Fermentation Of Edible Insectsmentioning
confidence: 99%
“…Enriched, printed, and baked snacks with ground insects were reported with a corresponding significant increase in the total essential amino acid, protein digestibility, and corrected amino acid score (Severini, Azzollini, et al 2018). Edible insects as novel and affordable sources of proteins in food have been reported and are known to contain appreciable bio-components with nutritional and therapeutic properties (Cho et al 2018;Cho et al 2019;Kewuyemi, Kesa, et al 2020). In light of the above reported studies on the printed food structures suggested being rich in healthpromoting components could, therefore, be potentially appreciated or improved through the bio-modification processes of fermentation or malting techniques (Adebo 2020;Ohanenye et al 2020).…”
Section: The Current State Of Research On 3d Printed Foods and Applicability For Fermented And Malted Foodsmentioning
confidence: 99%